Influences of Bi0.75Y0.25O1.5 addition on the microstructure and ionic conductivity of Ce0.8Y0.2O1.9 ceramics. Issue 4 (5th April 2021) - Liang, Wenke; Meng, Bin; Xiao, Qingfei; Ping, Xinyu; Zheng, Qian; Li, Chen; Xia, Zhidong
Abstract: A second phase of Y2 O3 ‐stabilized Bi2 O3 (Bi0.75 Y0.25 O1.5, YSB) is introduced into Y2 O3 ‐doped CeO2 (Ce0.8 Y0.2 O1.9, YDC) as a sintering additive and the composite ceramics of YDC‐xYSB (x = 0, 5, 10, 20, 30, 40 wt%) are prepared through sintering at 1100°C for 6 h in air atmosphere. The YDC‐xYSB ceramics are composed of both YDC and YSB with cubic fluorite structure, and no other impurity phases are detected in XRD patterns. The relative density of YDC‐xYSB rises firstly for x ≤5 wt%, and then it declines with YSB addition from 5 to 40 wt%. The average grain size of YDC decreases from 270 nm to 85.7 nm with YSB addition from 0 to 40 wt%. The YSB phase segregates at the grain boundaries of YDC based on the TEM analysis result. The ionic conductivity of YDC‐xYSB (x ≥5 wt%) is lower than that of YDC in the test temperature of 200°C–500°C, while it gradually exceeds that of YDC in 500°C–750°C. At 750°C, the conductivity of YDC‐30%YSB (6.22 × 10 −2  S/cm) is 1.35 times higher than that of YDC (4.6 × 10 −2  S/cm). The YSB addition can improve the ionic conductivity of YDC in 500°C–750°C and decrease its sintering temperature.